Comparing Models of the Children’s Yale-Brown Obsessive-Compulsive Scale (CY-BOCS) in an Italian Clinical Sample - Novara, Caterina; Pardini, Susanna; Cardona, Francesco; Pastore, Massimiliano (Frontiers in Psychiatry, 2020)
Background: Obsessive Compulsive Disorder (OCD) is a mental disorder that interferes with daily functioning and may arise during childhood. The current study is the first attempt by Italian researchers to validate the CY-BOCS. Aims: The study’s primary aim was to investigate the best CY-BOCS model fit, adopting a Bayesian model comparison strategy, confronting four different factors models: a one-factor model; a two-factor model based on Obsessions and Compulsions; Storch et al.’s and Mc Kay et al.’s two-factor model based on Disturbance and Severity. The study also aimed to investigate the types of treatment found in a sample of Italian OCD children patients. Methods: The study’s sample was made up of 53 children with OCD, 14 children with Tourette Syndrome and TIC. Results: An analysis of our data demonstrated that the Obsessions and Compulsions model was the most plausible one as it demonstrated the best fit indices, strong convergent validity and good reliability. Study results additionally uncovered that 24.5% of the children in the OCD sample had not yet begun any treatment pathway a year after a diagnosis was formulated. Conclusions: These findings suggest that the Obsessions and Compulsions scales of the CY-BOCS separately represent appropriate instruments to evaluate children with OCD.